FAITH BASE HIGHER EDUCATION : A SYSTEMATIC LITERATURE REVIEW OF FAITH BASED UNIVERSITY IMAGE STRATEGY - Yusnidar,; Sri indrastuti,; Annisa Mardatillah, (Proceeding International Conference on Social Sciences, 2026)
Article This aim study development and achievement latest study related to branding and image strategies institutions at faith-based universities . Approach systematic mapping study (SMS) and bibliometric study Scopus data -based used For identify trends , distribution publications , and structure collaboration researchers through analysis co-authorship use VOSviewer . SMS results show 130 documents fulfil criteria inclusion with publication beginning since 2000, dominated writer from America. Analysis bibliometrics show that cohesion collaboration writer start strengthen since 2023, Research This formulate 3 research questions that will be support search findings the latest one that is still can be explored in research furthermore